Knowledge and attitude on human papilloma virus among adolescent girls in school students at Puducherry - Arunachalam, D.; Subash Chandrabose, G. (International Journal Of Community Medicine And Public Health, 2019)
Background: Human papillomavirus (HPV) is one of the most common causes of sexually transmitted infections. About 50–80% of sexually active women are exposed to at least one HPV type during their lifetime. Methods: A descriptive study to assess the knowledge and attitude on human papilloma virus among adolescent girls belonging to selected school at Puducherry. The objectives of the study were to assess the knowledge and attitude regarding HPV among adolescent girls. Adolescent girls were selected on the basis of convenient sampling technique. Structured teaching program were provided for 60 adolescent girls. Questionnaires are given to the students, collected and data were analyzed using the SPSS version 20.0 software. Results: The data will be collected from adolescent girls in the age group of 13-18 years among selected school students. The results found that majority of adolescent girls having inadequate knowledge (56.7%). There are 36.7% of adolescent girls having moderately adequate knowledge and only 6.6% of adolescent girls are having adequate knowledge on HPV. Conclusions: The majority of the girls having poor knowledge and attitude on HPV. The students need to be encouraged to engage in safe sexual practice to prevent and reduce risk of HPV infection. They have suggested that awareness effective and cost effective in improving the knowledge and attitude on human papilloma virus and can be implemented in daily living to have a healthy life.